PENINGKATAN KEMAMPUAN GURU DALAM MENYUSUN RENCANA PELAKSANAAN PEMBELAJARAN (RPP) MELALUI PENDAMPINGAN PERIODIK KEPALA SEKOLAH DI SDN 3 ADISARA - Nur Rofiah (Dwija Inspira: Jurnal Pendidikan Multi Perspektif, 2018)
This research uses 2 (two) cycles with each cycle divided into group and periodic mentoring to classroom teachers and subject teachers. The following data: in cycle I that 4 teachers (50.00%) scored in the range of values 76-90 including both Good (B) and 4 teacher (50.00%) categories were scored in the 61-75 range including the category group Simply (C). The results of cycle II obtained data of 1 (one) teacher (12.5%) got the value in the range of values 91-100 including the category of Both Once (BS) and 7 (seven) teachers (87.5%) got value in the range of values 76-90 belongs to the Good Categories (B). From these data it can be concluded that periodic guidance can significantly improve teachers’ ability in making RPP.